1962
DOI: 10.1002/cpt19623116
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy in depressions: Controlled evaluation of imipramine, isocarboxazide, dextroamphetamine‐amobarbital, and placebo

Abstract: Controlled evaluation of imipramine, isocarboxazide, dextroamphetamine-amobarbital, and placeboAn evaluation of imipramine, isocarboxazide, dextroamphetamine-amobarbital, and placebo was carried out in 204 patients with depressive syndromes in thirty-two Veterans Administration Hospitals. Treatment with a fixed dosage schedule was followed for 3 weeks, the dosage becoming flexible during an ensuing 9 week period. Evaluation of responses was made by three rating scales specially derived for depressed patients.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Shepherd et al (1966) (Ball and Kiloh, 1959;Daneman, 1961;Abraham et al, 1963;Medical Research Council, 1965;Bassa and Vora, 1965) (Doust et al, 1959;Sloane et al, 1959;Roulet et al, 1962;Bassa and Vora, 1965;Friedman et al, 1966). In the remainder (Lehmann et al, 1958;Ball and Kiloh, 1959;Leyberg and Denmark, 1959;Holdway, 1960;Kenning et al, 1960;Miller et al, 1960;Agnew et al, 1961;Ashby and Collins, 1961;Daneman, 1961;Friedman et al, 1961;Hohn et al, 1961;Linford Rees et al, 1961;Rothman et al, 1961;Overall et al, 1962;Wittenborn et al, 1962;Abraham et al, 1963;Robin and Langley, 1964;Medical Research Council, 1965;Schorer et al, 1966) (Beck, 1967); instead, adverse verdicts have coincided with a waning interest and the drug has gained-on inadequate evidence-an established, if ill-defined, place in psychiatry.…”
Section: Characteristics Of Patients Studiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Shepherd et al (1966) (Ball and Kiloh, 1959;Daneman, 1961;Abraham et al, 1963;Medical Research Council, 1965;Bassa and Vora, 1965) (Doust et al, 1959;Sloane et al, 1959;Roulet et al, 1962;Bassa and Vora, 1965;Friedman et al, 1966). In the remainder (Lehmann et al, 1958;Ball and Kiloh, 1959;Leyberg and Denmark, 1959;Holdway, 1960;Kenning et al, 1960;Miller et al, 1960;Agnew et al, 1961;Ashby and Collins, 1961;Daneman, 1961;Friedman et al, 1961;Hohn et al, 1961;Linford Rees et al, 1961;Rothman et al, 1961;Overall et al, 1962;Wittenborn et al, 1962;Abraham et al, 1963;Robin and Langley, 1964;Medical Research Council, 1965;Schorer et al, 1966) (Beck, 1967); instead, adverse verdicts have coincided with a waning interest and the drug has gained-on inadequate evidence-an established, if ill-defined, place in psychiatry.…”
Section: Characteristics Of Patients Studiedmentioning
confidence: 99%
“…Five out of the 24 trials have returned adverse verdicts (Doust et al, 1959;Sloane et al, 1959;Roulet et al, 1962;Bassa and Vora, 1965;Friedman et al, 1966). In the remainder (Lehmann et al, 1958;Ball and Kiloh, 1959;Leyberg and Denmark, 1959;Holdway, 1960;Kenning et al, 1960;Miller et al, 1960;Agnew et al, 1961;Ashby and Collins, 1961;Daneman, 1961;Friedman et al, 1961;Hohn et al, 1961;Linford Rees et al, 1961;Rothman et al, 1961;Overall et al, 1962;Wittenborn et al, 1962;Abraham et al, 1963;Robin and Langley, 1964;Medical Research Council, 1965;Schorer et al, 1966) the verdicts are either generally favourable or else the allocation is difficult.…”
Section: Characteristics Of Patients Studiedmentioning
confidence: 99%
“…The clinical efficacy of isocarboxazid was never well established in randomized controlled trials [1,8] and for many years the clinical specificity of monoamine oxidase inhibitors in so-called atypical depression was intensely, however, inconclusively studied [9][10][11].…”
Section: The Clinical Efficacy Of Isocarboxazid In Monotherapy and Inmentioning
confidence: 99%
“…The usefulness of phenothiazine therapy in younger, newly‐admitted schizophrenic patients already has been demonstrated in several studies (1–3). Our one major investigation of depressed patients showed that imipramine was the most effective agent tested (4). The situation was less clear regarding the effect of combined drug therapy in patients with chronic schizophrenia (5).…”
Section: Field Station Principal Investigatormentioning
confidence: 99%